Competing with unicorns : how the world's best companies ship software and work differently - Rasmusson, Jonathan (Pragmatic programmers., 2020)
Massively successful tech companies-- Unicorns--have discovered how to take the techniques that made them successful as a startup and scale them to the enterprise level. Amazon, Facebook, Google, and Spotify all work like startups, despite having workforces numbering in the tens of thousands. Go behind the scenes with an Ex-Spotify engineer and coach, and learn to develop software the way the best companies do it. If you're a tech or product lead and you want to ship product better, this is your playbook. If you're an engineer, tester, analyst, or project manager, and you suspect there are better ways to work, you are correct. And if you're a manager, Agile coach, or some one charged with improving how your company ships software, this book will give you the tools, techniques, and practices of world's most innovative, delivery-focused companies. Don't just admire the top companies; learn from them.